2009
DOI: 10.1111/j.1365-2605.2007.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of seminal germ cells in azoospermia: correlations with testicular histology and TESE outcome

Abstract: In the treatment of male infertility by intra-cytoplasmic injection of spermatozoa (ICSI) extracted from testicular tissue (TESE), the high incidence of negative TESE outcome calls for non-invasive prognostic methods. Literature suggests that seminal haploid germ cell detection could be one. For this purpose, a multi-parametric stringent flow cytometric method was applied to 50 TESE patients for the quantification of ejaculated germ cells. Cells from 50 ejaculates were identified and quantified as spermatozoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Yeung et al showed that quantification of seminal IGCs in azoospermia using flow cytometry cannot predict TESE outcome. According to their conclusion, this inability could be due to the limitations of flow cytometry in differentiating between germ cells and other artifacts in semen precipitates [26]. In our pervious study, we demonstrated that concomitant detection of DAZ and PRM2 transcripts by RT-PCR in seminal fluid is able to predict the presence of spermatid/sperm in testis of NOA men [18].…”
Section: Discussionmentioning
confidence: 84%
“…Yeung et al showed that quantification of seminal IGCs in azoospermia using flow cytometry cannot predict TESE outcome. According to their conclusion, this inability could be due to the limitations of flow cytometry in differentiating between germ cells and other artifacts in semen precipitates [26]. In our pervious study, we demonstrated that concomitant detection of DAZ and PRM2 transcripts by RT-PCR in seminal fluid is able to predict the presence of spermatid/sperm in testis of NOA men [18].…”
Section: Discussionmentioning
confidence: 84%
“…The probability rate for unbalanced progeny with trisomy/monosomy of the 9p11.2 segment after adjacent-1 segregation at birth for paternal carriers was estimated at 11.8%, and the odds of unbalanced progeny at prenatal diagnosis was 57% [49]. The probability of natural conception was very low, but an option for ICSI after testicular biopsy and pre-implantation genetic diagnosis was discussed with the couple because the presence of immature germ cells in the ejaculate could indicate spermatogenic activity in the testes [50]. Unfortunately, bilateral testicular biopsies did not reveal any sperm cells (N. Huleyuk, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The latter score count reveals close correlation with TESE results when using cryopreserved testicular tissue for diagnostic purposes before hormonal stimulation of the female partner and ICSI (unpublished data). Detection of immature germ cells in semen, however, does not provide a prognostic marker for successful TESE, although their presence could indicate the spermatogenic activity within the testis (Yeung et al. , 2007).…”
Section: Prognosis Of Male Factor Infertility: Sperm Retrieval and Fementioning
confidence: 99%